Friend or Fraud? Exploring Foreign Language Students’ Awareness of AI-Generated Content - Sitti Aminah; Akmal; Atmarani Dewi Purnama (Universitas Islam Ahmad Dahlan (UIAD), 2025)
This study aims to explore the awareness of students majoring in Arabic Language Education and English Language Education at Ahmad Dahlan Islamic University, Sinjai, regarding content generated by artificial intelligence (AI). In today's digital era, many students utilize AI tools to complete academic assignments, but not all are aware of the difference between human-generated and machine-generated content. This study employed a quantitative method with a survey approach, involving 42 students. Data were collected through online questionnaire with Likert scale and were analyzed using descriptive statistical techniques, including mean scores and percentage distributions. The result showed that students were quite familiar with the use of AI, especially for translation and grammar correction purposes. However, their level of awareness in critically evaluating AI-generated content, especially in distinguishing between human and machine-generated writing, was in the moderate category. From an ethical perspective, most respondents expressed a positive attitude towards the responsible use of AI in learning and rejected academic dishonesty practices involving the unethical use of AI content. These results suggest that while AI functions as a “friend” by assisting language learning, it also has the potential to become a “fraud” when students lack sufficient critical awareness and ethical guidance. Overall, this study concludes that the role of AI in foreign language education depends largely on students’ critical awareness, ethical attitudes, and institutional guidance. Strengthening critical digital literacy and establishing clear academic policies are therefore essential to ensure responsible AI integration.